2004
DOI: 10.1007/s00425-004-1433-0
|View full text |Cite
|
Sign up to set email alerts
|

The tomato early fruit specific gene Lefsm1 defines a novel class of plant-specific SANT/MYB domain proteins

Abstract: We describe here a novel plant-specific gene, Lefsm1 (fruit SANT/MYB-like 1) harboring a single SANT/MYB domain. The expression of Lefsm1 is specific to the very early stages of tomato (Lycopersicon esculentum) fruit development. Ectopic expression of Lefsm1 results in severe developmental alterations manifested in retarded growth, and reduced apical dominance during tomato and Arabidopsis seedling development. A promoter sequence residing 1.0 kb upstream to the translation initiation codon confers the organ-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 51 publications
2
47
0
3
Order By: Relevance
“…However, both ends of this gene and some segments of the central region is highly conserved. However some parts of central regions vary (see screening of the alignment of orthologous genes in Figure S10) [56,57].…”
Section: Positively Selected Genes In M Oleifera Genomementioning
confidence: 99%
“…However, both ends of this gene and some segments of the central region is highly conserved. However some parts of central regions vary (see screening of the alignment of orthologous genes in Figure S10) [56,57].…”
Section: Positively Selected Genes In M Oleifera Genomementioning
confidence: 99%
“…9).Proteins with the domains of MYB or SANT were likely to participate in the regulation of plant flowering and early-fruit development (Barg et al, 2005;Choi et al, 2007). A highest percentage of identity (41%) and query coverage (27%) were detected between our sequence and the genes of both Trichorapa and Euphratica species.…”
Section: Sequence Analysis Of Some Polymorphic Pcr Bandsmentioning
confidence: 86%
“…Phylogenetic analysis of the deduced amino acid sequences of these genes and those of the orthologs in other plants showed that the torenia genes were highly similar to the orthologs of A. majus ( Fig. 3a, b; Barg et al, 2005;Baxter et al, 2007;Machemer et al, 2011;MartĂ­n-Trillo and Cubas, 2010). The TCP domain for DNA binding activity, R domain involved in the CYC/TB1 family of TCP genes, and ECE motif were conserved in TfCYC1, 2, and 3 ( Fig.…”
Section: Structure and Expression Analyses Of Floral Symmetry Associamentioning
confidence: 86%
“…In TfRAD1 and 2, structures characteristic of RAD were also conserved; thus, only the MYBI domain and the CREB motif for DNA binding activity at the C terminus were detected ( Fig. 4b; Barg et al, 2005).…”
Section: Structure and Expression Analyses Of Floral Symmetry Associamentioning
confidence: 99%